2012
DOI: 10.1136/flgastro-2012-100133
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor complaints in gastroenterology practice: results of a survey in the netherlands

Abstract: ObjectiveThe pelvic floor is an integrated structure; dysfunctions may lead to a wide range of symptoms, involving voiding, defecation and sexual functioning (SF). Functional symptoms such as constipation and lower abdominal pain are often caused by pelvic floor dysfunction (PFD), and they highly impact the quality of life. Multiple specialists are responsible for a specific part of the pelvic floor, but its treatment asks for a holistic approach. The authors are still unaware of gastroenterologists' knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our findings are in line with the conclusions of the European Association of Urology guidelines‐ that voiding dysfunction often occurs in association with other PFDs, such as FI and sexual problems . Faecal problems have also been associated with a negative impact on sexual function …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with the conclusions of the European Association of Urology guidelines‐ that voiding dysfunction often occurs in association with other PFDs, such as FI and sexual problems . Faecal problems have also been associated with a negative impact on sexual function …”
Section: Discussionsupporting
confidence: 92%
“…In a survey Nicolai et al assessed whether or not gastroenterologists addressed male's sexual function during consultation for intestine, colon, or anorectal problems. They revealed that only 2.5% did so.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are very likely to have a dysfunction of the pelvic floor and might need to be referred to a pelvic floor physiotherapist, sexologist, urologist or a psychologist to treat the globality of their complaints. This is probably due to a lack of experience in this field or a lack of time in their daily practice [11].…”
Section: Dear Editormentioning
confidence: 99%